Geschlecht - Sozialisation - Transformationen - Dausien, Bettina; Thon, Christine; Walgenbach, Katharina (Jahrbuch Frauen- und Geschlechterforschung in der Erziehungswissenschaft, 2016)
Since the fundamental critique of the assumption of "female socialization" in gender studies, the question of how individuals grow into a gender-structured society has long been considered outdated. In order to contribute to a revitalization of the debate on socialization in gender studies, the authors consider this question both in terms of the transformations of the theoretical debate and in terms of the changes in social gender relations.